Innovative Community Empowerment through a Student-Led KKN in Durung 2 Village - Rialdy, Novien (PT Agung Media Publisher, 2025)
This community service program was designed to introduce an innovative student-led KKN model that integrates anti-bullying education, social-values reinforcement, and microenterprise (UMKM) digital empowerment in Durung 2 Village, Medan Marelan. The program responds to persistent challenges in child protection, community cohesion, and the limited digital readiness of micro-entrepreneurs. The intervention was implemented over ten days and involved elementary-school children, UMKM owners, community leaders, and student volunteers. Activities included anti-bullying awareness sessions, 5S social-value campaigns, basic literacy tutoring, morning exercise and community clean-up, UMKM mentoring on branding and packaging, HPP calculation training, and the introduction of QRIS digital payments. Data were collected through observation, attendance records, participant feedback, and the official KKN field report, then analyzed descriptively to identify outputs and challenges. The student-led KKN successfully implemented all planned activities and achieved immediate improvements in children's understanding of bullying, strengthened community interaction, and enhanced UMKM identity through new logos, packaging recommendations, and basic digital-payment adoption. Some UMKM participants demonstrated increased interest in branding and more accurate cost calculations. However, limited time, low digital literacy, inadequate tools, and capital constraints presented notable challenges. The integration of play-based anti-bullying education aligns with prior evidence that interactive pedagogies increase empathy and reduce aggressive behaviors. Likewise, the provision of branding assistance and QRIS introduction supports broader national efforts to digitize UMKM operations.